2018
DOI: 10.1128/iai.00921-17
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma bovis-Induced Inhibition of Bovine Peripheral Blood Mononuclear Cell Proliferation Is Ameliorated after Blocking the Immune-Inhibitory Programmed Death 1 Receptor

Abstract: -induced immune suppression is a major obstacle faced by the host for controlling infections. impairment of antigen-specific T-cell responses is achieved through inhibiting the proliferation of peripheral blood mononuclear cells (PBMCs). This impairment may contribute to the persistence of infection in various sites, including lungs, and its systemic spread to various organs such as joints, with the underlying mechanisms remaining elusive. Here, we elucidated the role of the immune-inhibitory receptor programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…High amounts of strain L22/93 associated with cells even led to an anti-proliferative response of primary epithelial cells. The same observation was also previously made with PBMCs (Suleman et al, 2018 ). However, the in vivo relevance of this finding is not clear.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…High amounts of strain L22/93 associated with cells even led to an anti-proliferative response of primary epithelial cells. The same observation was also previously made with PBMCs (Suleman et al, 2018 ). However, the in vivo relevance of this finding is not clear.…”
Section: Discussionsupporting
confidence: 82%
“…Infected PBMCs were studied, considering cytotoxic effects, induction of apoptosis and viability of host cells, but results were inconsistent (Vanden Bush and Rosenbusch, 2002 ; van der Merwe et al, 2010 ; Gondaira et al, 2015 ). However, M. bovis was shown to inhibit proliferation of PBMCs (Vanden Bush and Rosenbusch, 2002 ; van der Merwe et al, 2010 ; Suleman et al, 2016 , 2018 ). Studies analyzing distinct blood cell types gave clearer results.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine leukemia virus causes progressive exhaustion of T cell functions by up-regulation of programmed death-1 (PD-1) and lymphocyte activation gene-3 [ 42 ], and blockage of its receptor PD-L1 leads to enhancement of antiviral responses [ 43 ]. Certain bovine respiratory complex pathogens like Mycoplasma bovis strongly inhibit lymphoproliferation of CD4+ and CD8+ T cells during infection [ 44 ]. Anaplasma marginale is also known to downregulate antigen-specific T and B cells leading to a failure to establish effective memory T cell responses and persistent infection [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…T-cells showed a substantial decrease in CD4 PD1 and CD8 PD1 subsets and a significant increase in CD4 PD1 and CD8 PD1 subsets. Furthermore, the use of blocking PD-1 antibodies results in the restoration of M. bovis strain Mb1 after PD-1/PD-L1 destruction as well as the proliferation of M. bovis strain Mb1 in contaminated PBMCs [ 31 ]. A recent study showed that PD-1/PD-L1 ( Figure 3 ) is important for Mycoplasma bovis pathogenesis and related immune exhaustion in inhibitory pathways, resulting in compromised host immune responses [ 31 ].…”
Section: Strategies Associated With the Hostmentioning
confidence: 99%
“…Inconsistent findings on PBMC contamination by M. bovis have been obtained regarding apoptosis induction, cytotoxic effects, and the host cells’ viability [ 8 , 28 , 29 , 30 ]. Similarly, Mycoplasma bovis has been found to inhibit the development of PBMCs [ 8 , 29 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%